HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN MP-ASI DENGAN KEJADIAN STUNTING DI DESA SELOK ANYAR KECAMATAN PASIRIAN KABUPATEN LUMAJANG - Rahmawati, Isti; Zakiyyah, Muthmainnah; Hikmawati, Nova (NHM PRESS, 2023)
Stunting is a form of nutritional disorder in terms of body size which is characterized by a short body condition compared to children his age. Stunting is influenced by many things, one of which is children's nutritional intake. The impact of stunting caused in the short term is the disruption of brain development, impaired intelligence, physical growth, and impaired body metabolism. In the long term, it causes decreased cognitive ability, learning achievement, and decreased immunity so that it is easy to get sick. The purpose of this study was to determine the correlation between the mother's level of knowledge about the pattern of giving complementary feeding and the incidence of stunting in Selok Anyar village. This research is an observational study with a cross-sectional design conducted in July 2023. The population in this study was 50 children aged 6-36 months with a total sample of 33 samples. The results of this study showed as many as 33 samples (60.60%) with a good level of knowledge, and as many as 20 children (60.60%) with normal nutritional status. The results of the chi square statistic correlation test showed that there was a correlation between themother's level of knowledge and the incidence of stunting (p=0.000).